Evaluating the Effectiveness of Outcome-Based Education in Indian Engineering Programs (International Journal of Food and Nutritional Sciences, 2022)
Outcome-Based Education (OBE) has emerged as a pivotal development in Indian engineering education in recent years. This approach marks a significant shift from a teacher-centric to a student-centric learning paradigm. While OBE has been implemented globally since the 1990s, its adoption in India followed the signing of the Washington Accord. The National Board of Accreditation (NBA), the apex body responsible for monitoring the quality of engineering education in India, has mandated OBE as a part of the accreditation process. Although the positive outcomes of OBE in engineering education are evident, the preparedness of faculty members to implement this strategy remains a critical question. This paper examines the impact of OBE on Indian engineering education through a survey-based study. The findings are promising, indicating that the principles of OBE—such as curriculum design, delivery, assessment, evaluation, and reflection—are increasingly being integrated into engineering education in India. However, additional training in certain areas is still necessary.